2019
DOI: 10.1371/journal.pone.0220307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of flow cytometry for the detection of bacteria in biological fluids

Abstract: Objectives Conventional microbiological procedures for the isolation of bacteria from biological fluids consist of culture on solid media and enrichment broth. However, these methods can delay the microbiological identification for up to 4 days. The aim of this study was to evaluate the analytical performance of Sysmex UF500i (Sysmex, Kobe, Japan) as a screening method for the detection of bacteria in different biological fluids in comparison with direct Gram staining and the conventional culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 34 publications
4
5
0
1
Order By: Relevance
“…Also, samples with culture-positive results had significantly higher bacterial and WBC counts than samples with culture-negative results. Our results are in agreement with previous studies which have demonstrated that bacterial count by FCM showed a good correlation with culture results 6,8,10,11 . We established optimal cut-off points for bacterial count by FCM in order to obtain DGS and culture-positive results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, samples with culture-positive results had significantly higher bacterial and WBC counts than samples with culture-negative results. Our results are in agreement with previous studies which have demonstrated that bacterial count by FCM showed a good correlation with culture results 6,8,10,11 . We established optimal cut-off points for bacterial count by FCM in order to obtain DGS and culture-positive results.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the differential leukocyte counts, UF4000 (Sysmex, Kobe, Japan) showed excellent performance for body fluids which did not contain abnormal cells. Our results are in agreement with those of other studies, having demonstrated that the FCM allows to correctly classify and enumerate WBCs in the CSF, PRF and PDF [5][6][7][8][9][10] . Due to its characteristics, the XN10 (Sysmex, Kobe, Japan) is suitable for the analysis of samples containing a large quantity of RBC and WBC (> 10 3 / µL).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the differential leukocyte counts, UF4000 (Sysmex, Kobe, Japan) showed excellent performance for body fluids which did not contain abnormal cells. Our results agree with those of other studies, having demonstrated that the FCM allows to correctly classify and enumerate WBCs in the CSF, PRF and PDF ( 5 10 ). Because of its characteristics, the XN10 (Sysmex, Kobe, Japan) is suitable for the analysis of samples containing a large quantity of RBC and WBC (>10 3 /μL).…”
Section: Discussionsupporting
confidence: 93%
“…Another useful technique capable of providing direct bacterial quantification is flow cytometry. Although it has mostly been employed to investigate bacterial physiology and metabolic responses [82], efforts to optimize its quantification ability have made it suitable for some diagnostic applications [83]. In particular, flow cytometry analysis and imaging now enable detection and enumeration of non-culturable and intracellular P. aeruginosa cells [84,85].…”
Section: P Aeruginosa Vbnc Cell Detection and Quantification In Cf Respiratory Samples 41 Total Live Cell Detection Strategiesmentioning
confidence: 99%